Advances in Human–Machine Systems, Human–Machine Interfaces and Human Wearable Device Performance - Kai Way Li; Lu Peng (Applied Sciences)
The human–machine system (HMS) and human–machine interface (HMI) are among the top factors that affect the development of advanced systems, equipment, and products [...]